Low-bulk-density ultra-high molecular weight polyethylene and preparation method thereof

By using a catalyst to mix metal organic framework particles in the polymerization reaction, the problem of difficulty in developing low bulk density ultra-high molecular weight polyethylene materials in the prior art is solved, and the low bulk density characteristics and simplicity of operation of the product are achieved, and it is suitable for the preparation of microporous filtration materials.

CN119798498AActive Publication Date: 2025-04-11WANHUA CHEM GRP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510000907.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11
Estimated Expiration
2045-01-02

AI Technical Summary

Technical Problem

The prior art is difficult to develop low-packet density ultra-high molecular weight polyethylene materials suitable for microporous filtration materials, and the production process is complex and there are cumbersome steps to remove inorganic impurities.

Method used

By mixing catalyst A with metal organic framework (MOF) particles and polymerizing in a reactor containing inert solvent and cocatalyst B, rapid growth of ultra-high molecular weight polyethylene chains is achieved to form a product with low bulk density.

Benefits of technology

It realizes the low bulk density characteristics of ultra-high molecular weight polyethylene materials, and is suitable for the preparation of microporous filter materials. It is simple to operate and has high practical value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225073660000081
    Figure BDA0005225073660000081
Patent Text Reader

Abstract

The invention discloses a preparation method of ultra-high molecular weight polyethylene with low bulk density, which comprises the following steps: uniformly mixing a catalyst and metal organic framework (MOF) particles, adding the mixture into an inert alkane solvent, and introducing ethylene and a small amount of hydrogen to carry out polymerization reaction to obtain the ultra-high molecular weight polyethylene. The obtained material has the following characteristics: (a) the viscosity average molecular weight is in a range of 4-9 million; (b) a particle diameter (D50) of 60 [mu] m < = D50 < = 130 [mu] m; and (c) the bulk density is 0.2-0.35 g / cm < 3 >. The ultra-high molecular weight polyethylene material obtained by the invention is suitable for producing a microporous filter material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer preparation, and more specifically, relates to a low bulk density ultra-high molecular weight polyethylene material and a preparation method thereof. Background Art

[0002] Ultra-high molecular weight polyethylene (UHMWPE) generally refers to linear polyethylene with a relative molecular mass of more than 1.5 million g / mol. Compared with ordinary polyethylene, it has significant advantages such as high impact resistance, extremely high wear resistance, high corrosion resistance, self-lubrication, environmental stress cracking resistance, chemical resistance and low temperature resistance, safety and hygiene, etc. It is widely used in textile, papermaking, food, chemical, packaging, agriculture, construction, medical, water purification, sports, entertainment, military and other fields.

[0003] The bulk density of general-purpose ultra-high molecular weight polyethylene materials on the market is generally 0.40-0.50 g / cm 3 There is still little progress in the development of low bulk density ultra-high molecular weight polyethylene resin particles suitable for microporous filtration materials.

[0004] Patent CN200580039390.2 discloses ethylene polymer microparticles and catalysts for their manufacture, wherein at least 95% of the weight ratio of the polymer microparticles passes through a 37-micron mesh sieve, and the median diameter (d50) measured by laser diffraction scattering is 3μm≤d50≤25μm. The bulk density of the particles prepared by this technology is not listed, and the polymer requires a cumbersome step of removing inorganic impurities. Patent 202211153833.2 discloses a class of ultra-high molecular weight polyethylene microparticles, with a small particle size and a small particle bulk density, a viscosity-average molecular weight in the range of 1-5 million, a particle median diameter (d50) of 40μm<d50<80μm, and a powder bulk density of 0.25-0.33g / cm 3 The invention only produces low bulk density products by adjusting the Zigeler-Natta catalyst preparation process, but lacks a method for producing low bulk density ultra-high molecular weight polyethylene products using metallocene catalysts and non-metallocene catalysts.

[0005] Therefore, in view of the problems existing in the prior art, it is necessary to develop a method for synthesizing a low bulk density ultra-high molecular weight polyethylene material suitable for microporous filter materials based on the existing multiple polyethylene catalyst systems. Summary of the invention

[0006] In view of the above problems, the present invention proposes a method for preparing a low bulk density ultra-high molecular weight polyethylene material. The ultra-high molecular weight polyethylene chain grows rapidly, and finally presents a popcorn-like appearance. The product has the characteristics of low bulk density. The production operation is simple and easy, and does not affect the ash content of the product, etc., and has high practical value.

[0007] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows:

[0008] A method for preparing a low bulk density ultra-high molecular weight polyethylene material comprises the following steps:

[0009] S1: Mix catalyst A and metal organic framework (MOF) particles evenly, add them into a reactor containing an inert solvent and a co-catalyst B and disperse them evenly;

[0010] S2: Ethylene and hydrogen are introduced into the reactor to carry out polymerization reaction to obtain polymer slurry, and ultra-high molecular weight polyethylene is separated.

[0011] Metal organic framework materials (MOF) can effectively capture ethylene due to their suitable pore size, achieving the enrichment of ethylene in inert solvents. In the early stage of ethylene polymerization, the catalyst can contact a large amount of ethylene, achieving the rapid growth of ultra-high molecular weight polyethylene chains. The prepared product can have the characteristics of low bulk density, which is suitable for further preparation of microporous filtration materials.

[0012] Furthermore, the catalyst A in S1 is selected from a Zigeler-Natta catalyst containing Ti, a metallocene catalyst and a non-metallocene catalyst, preferably a Zigeler-Natta catalyst. Common ZN catalysts include titanium tetrachloride, chromium oxide, etc.; metallocene catalysts include transition metal element complexes such as Ti, Zr, Hf as main catalysts, and alkylaluminoxane MAO as co-catalysts; the metal center of the non-metallocene catalyst is also an organic metal complex of a transition metal element or a part of the main group metal element.

[0013] Furthermore, the cocatalyst B comprises an alkyl aluminum compound, preferably one or more of methylaluminoxane, triethylaluminum, and triisobutylaluminoxane.

[0014] Furthermore, the molar ratio of the main catalyst A calculated as Ti element to the co-catalyst B calculated as aluminum element is 1:(10-5000), preferably 1:(25-2000).

[0015] Furthermore, the inert solvent is a straight-chain alkane with 5 to 10 carbon atoms, preferably one or more of n-pentane, n-hexane, cyclohexane, n-heptane, n-octane and n-decane. Preferably, the mass ratio of catalyst A to inert solvent is 1:(3*10 5 -15*10 5 ), more preferably 1:(5*10 5 -10*10 5 ).

[0016] Furthermore, the metal center selected for the MOF particles in S1 includes but is not limited to Cu, Zn, Ti, Cr, preferably Cu; the organic ligand includes but is not limited to benzene-1,3,5-tricarboxylic acid, terephthalic acid, 2-aminoterephthalic acid, 2,5-dioxy-1,4-benzenedicarboxylic acid, preferably benzene-1,3,5-tricarboxylic acid.

[0017] Furthermore, the mass ratio of the catalyst A to the MOF is 1:(0.1-10), preferably 1:(0.8-5).

[0018] Furthermore, the synthesis temperature of the ultra-high molecular weight polyethylene described in S2 is 40°C to 60°C, preferably 45°C to 55°C; the pressure is 0.6 to 2MPa, preferably 0.8 to 1.5MPa; and the polymerization reaction time is 2-6h, preferably 2.5 to 5h.

[0019] The second aspect of the present invention provides an ultra-high molecular weight polyethylene material with low bulk density prepared by the method:

[0020] (a) The viscosity average molecular weight is in the range of 3-10 million.

[0021] (b) particle size (D50) 50 μm ≤ D50 ≤ 150 μm;

[0022] (c) Bulk density is 0.2-0.35 g / cm 3 .

[0023] Furthermore, the viscosity average molecular weight of the material is in the range of 4-8 million.

[0024] Furthermore, the particle size of the material is 60 μm≤D50≤130 μm.

[0025] Furthermore, the bulk density of the material is 0.2-0.30 g / cm 3 .

[0026] Through the above technical scheme, the preparation method of ultra-high molecular weight polyethylene and the ultra-high molecular weight polyethylene provided by the present invention obtain the following beneficial effects: the present invention utilizes the porous structure of the MOF material to enrich ethylene, effectively improves the catalyst efficiency, and realizes the rapid growth of ultra-high molecular weight polyethylene chains. The product has the characteristics of low bulk density, is simple and easy to operate, and has high practical value. DETAILED DESCRIPTION

[0027] The technical solution of the present invention is further described in detail below through specific embodiments. However, it is necessary to point out that the following embodiments are only used to describe the content of the invention and do not constitute a limitation on the protection scope of the present invention.

[0028] In order to better describe the preparation method of the low bulk density ultra-high molecular weight polyethylene material provided by the present invention, the following examples may be described in a different order from that in the invention content of the specification, but it will not affect the understanding of the invention content by those skilled in the art.

[0029] Molecular weight of polymer: measured by viscosity method, using decahydronaphthalene as solvent, temperature 135°C, using Ubbelohde viscometer to measure the time it takes for the polymer solution to flow out, and then calculate the intrinsic viscosity η of the polymer. According to the formula

[0030] M = 5.37 × 10 4 ×(η) 1.37

[0031] The obtained M is the molecular weight of the polymer.

[0032] The particle size distribution of the polymer was measured using a Malvern S-type particle size analyzer.

[0033] Bulk density of polymer: refer to GB / T16913.1-1997: plug the outlet of the funnel with a stopper rod, put a certain amount of polymer powder into the density cup of the powder natural bulk density meter, scrape it flat with a scraper and pour it into the funnel, pull out the stopper rod to let the powder fall freely into the density cup at the bottom, and after all the powder flows out, use a scraper to scrape off the powder accumulated on the top of the density cup, weigh the density cup filled with powder, remove the tare weight, and get the weight of the polymer powder. Bulk density value = measured weight / measured volume. The unit is g / cm 3 The arithmetic mean of the two measured values ​​was recorded as the measurement result.

[0034] The MOF materials used in the examples were purchased from Beijing Inokai Technology Co., Ltd., with the grades HKUST-1, MIL-53, MIL-101, and MOF-74;

[0035] The catalysts used in the examples were purchased from Beijing Aoda Branch of Sinopec Catalyst Co., Ltd. BCE-H100 and NTR-971; the metallocene catalyst MAO-CAT1 and non-metallocene NMAO-CAT1 catalysts used were both from Wanhua Chemical Group Co., Ltd.

[0036] Example 1

[0037] The 5L polymerization kettle was evacuated and replaced with nitrogen, 3L cyclohexane and 2mL triethylaluminum were added, the stirring speed was controlled at 250rpm, 2mg BCE-H100 catalyst (Ti element accounted for 1.7wt%) of Beijing Aoda Branch of Sinopec Catalyst Co., Ltd. and 20mg MOF HKUST-1 material were mixed evenly, and then 10mL cyclohexane was used to flush the mixture of BCE-H100 catalyst and HKUST-1 into the polymerization kettle, and then ethylene gas was introduced to make the pressure in the kettle reach 0.6MPa, and the temperature in the kettle was controlled to 60℃. After 5h of polymerization, ethylene was stopped, the gas in the system was vented and the material was discharged, and granular polymer was obtained after drying. The properties of the polymer particles are shown in Table 1.

[0038] Example 2

[0039] The 5L polymerization kettle was evacuated and replaced with nitrogen, 1.5L of n-pentane and 1mL of triisobutylaluminoxane were added, the stirring speed was controlled at 250rpm, 2mg of Wanhua Chemical MAO-CAT1 catalyst (Ti element accounted for 8.3wt%) and 1.6mg of MOFMIL-53 material were mixed evenly, and then 10mL of n-pentane was used to flush the mixture of MAO-CAT1 catalyst and MIL-53 into the polymerization kettle, and then ethylene gas was introduced to make the pressure in the kettle reach 2MPa, and the temperature in the kettle was controlled to be 55°C. After 6h of polymerization, ethylene was stopped, the gas in the system was vented and the material was discharged, and a granular polymer was obtained after drying. The properties of the polymer particles are shown in Table 1.

[0040] Example 3

[0041] The 5L polymerization kettle was evacuated and replaced with nitrogen, 2L of n-hexane and 4mL of triethylaluminum were added, the stirring speed was controlled at 250rpm, 2mg of BCE-H100 catalyst (Ti element accounted for 1.7wt%) of Beijing Aoda Branch of Sinopec Catalyst Co., Ltd. and 2.4mg of MOF MIL-101 material were mixed evenly, and then 10mL of n-hexane was used to flush the mixture of BCE-H100 catalyst and MIL-101 into the polymerization kettle, and then ethylene gas was introduced to make the pressure in the kettle reach 0.8MPa, and the temperature in the kettle was controlled to be 55°C. After 3h of polymerization, ethylene was stopped, the gas in the system was vented and the material was discharged, and a granular polymer was obtained after drying. The properties of the polymer particles are shown in Table 1.

[0042] Example 4

[0043] The 5L polymerization kettle was evacuated and replaced with nitrogen, 1L of n-heptane and 10mL of methylaluminoxane were added, the stirring speed was controlled at 250rpm, 2mg of Wanhua Chemical NMAO-CAT1 catalyst (Ti element accounted for 6.1wt%) and 10mg of MOF MIL-101 material were mixed evenly, and then 10mL of n-heptane was used to flush the mixture of NMAO-CAT1 catalyst and MIL-101 into the polymerization kettle, and then ethylene gas was introduced to make the pressure in the kettle reach 1.5MPa, and the temperature in the kettle was controlled to 45°C. After 2h of polymerization, ethylene was stopped, the gas in the system was vented and the material was discharged, and a granular polymer was obtained after drying. The properties of the polymer particles are shown in Table 1.

[0044] Example 5

[0045] The 5L polymerization kettle was evacuated and replaced with nitrogen, 4L of n-octane and 6mL of triethylaluminum were added, the stirring speed was controlled at 250rpm, 2mg of NTR-971 catalyst (Ti element accounted for 1.48wt%) from Beijing Aoda Branch of Sinopec Catalyst Co., Ltd. and 0.2mg of MOF MOF-74 material were mixed evenly, and then 10mL of n-octane was used to flush the mixture of NTR-971 catalyst and MOF-74 into the polymerization kettle, and then ethylene gas was introduced to make the pressure in the kettle reach 0.8MPa, and the temperature in the kettle was controlled to be 40°C. After 2.5h of polymerization, ethylene was stopped, the gas in the system was vented and the material was discharged, and a granular polymer was obtained after drying. The properties of the polymer particles are shown in Table 1.

[0046] Comparative Example 1

[0047] The difference between this comparative example and Example 1 is that the MOF material is not added into the reactor, and the same polymerization conditions are adopted. The properties of the polymer particles are shown in Table 1.

[0048] Comparative Example 2

[0049] The difference between this comparative example and Example 1 is that the catalyst is first added to the reactor and then the MOF material is added. The same polymerization conditions are adopted. The properties of the polymer particles are shown in Table 1.

[0050] Table 1

[0051]

[0052] It can be seen from the above embodiments that the preparation method of ultra-high molecular weight polyethylene and the ultra-high molecular weight polyethylene provided by the present invention have the characteristics of low bulk density, are simple and easy to operate, have high practical value and have good industrial application prospects.

Claims

1. A method for preparing a low bulk density ultra-high molecular weight polyethylene material, characterized in that: The preparation method comprises the following steps: S1, mixing catalyst A and metal organic framework MOF particles uniformly, adding them into a reactor containing an inert solvent and a co-catalyst B and dispersing them uniformly; S2. Ethylene and hydrogen are introduced into the reactor to carry out polymerization reaction to obtain polymer slurry, and ultra-high molecular weight polyethylene is obtained by separation.

2. The preparation method according to claim 1, characterized in that: S1 The catalyst A is selected from a Zigeler-Natta catalyst containing Ti, a metallocene catalyst and a non-metallocene catalyst, preferably a Zigeler-Natta catalyst.

3. The preparation method according to claim 1 or 2, characterized in that: S1 The cocatalyst B comprises an alkyl aluminum compound, preferably one or more of methylaluminoxane, triethylaluminum, and triisobutylaluminoxane.

4. The preparation method according to claim 3, characterized in that: The molar ratio of the main catalyst A calculated as Ti element to the co-catalyst B calculated as aluminum element is 1:(10-5000), preferably 1:(20-2000).

5. The preparation method according to any one of claims 1 to 4, characterized in that: The inert solvent is a straight-chain alkane with 5 to 10 carbon atoms, preferably one or more of n-pentane, n-hexane, cyclohexane, n-heptane, n-octane, and n-decane; preferably, the mass ratio of catalyst A to inert solvent is 1:(3*10 5 -15*10 5 ), more preferably 1:(5*10 5 -10*10 5 ).

6. The preparation method according to any one of claims 1 to 5, characterized in that: The metal center selected for the MOF particles in S1 includes but is not limited to Cu, Zn, Ti, Cr, preferably Cu; the organic ligand includes but is not limited to benzene-1,3,5-tricarboxylic acid, terephthalic acid, 2-aminoterephthalic acid, 2,5-dioxy-1,4-benzenedicarboxylic acid, preferably benzene-1,3,5-tricarboxylic acid.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The mass ratio of the catalyst A to the MOF is 1:(0.1-10), preferably 1:(0.8-5).

8. The preparation method according to any one of claims 1 to 7, characterized in that: The synthesis temperature of the ultra-high molecular weight polyethylene in S2 is 40°C to 60°C, preferably 45°C to 55°C; the pressure is 0.6 to 2MPa, preferably 0.8 to 1.5MPa; and the polymerization reaction time is 2-6h, preferably 2.5 to 5h.

9. The ultra-high molecular weight polyethylene material obtained by the method according to any one of claims 1 to 8, characterized in that: The viscosity average molecular weight of the material is in the range of 3-10 million, preferably in the range of 4-8 million; the particle size (D50) is 50 μm≤D50≤150 μm, preferably 60 μm≤D50≤130 μm; Bulk density is 0.2-0.35g / cm 3 , preferably 0.2-0.30g / cm 3 .

Citation Information

Patent Citations

  • Ethylene polymer fine particles, functional group-containing ethylene polymer fine particles, and catalyst carrier for production thereof

    CN101061144A

  • A type of fine particle size, low bulk density ultra-high molecular weight polyethylene powder

    CN116535551B

  • Novel urea-box linear low density polyethylene and preparing method thereof

    CN108467443A

  • Low-bulk-density ultra-high molecular weight polyethylene micro powder

    CN114249851A

  • Supported metallocene catalyst and preparation method and application thereof

    CN118834311A